2022
DOI: 10.3389/fcvm.2022.881946
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Frailty and New-Onset Atrial Fibrillation/Flutter Among Elderly Hypertensive Patients

Abstract: BackgroundFrailty was found to be common in patients with atrial fibrillation/flutter (AF), but there was still a lack of evidence regarding the relationship between frailty and new-onset AF.MethodsWe performed a post hoc analysis of data from the Systolic Blood Pressure Intervention Trial (SPRINT). In addition, we evaluated the relationship between baseline frailty status and new-onset AF in older adult patients with hypertension.ResultsIn total, 7,316 participants were included in our analysis, and a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A recently published cohort study from AHA by Orkaby et al did not show a statistically significant relationship between frailty and AFIB [ 22 ]. In contrast, another study by Hang et al showed a statistically significant relationship between frailty and first-onset AFIB in patients with arterial hypertension [ 23 ]. The degree of frailty in the elderly and the development of AFIB share common pathophysiological mechanisms such as a strong inflammatory response, poor immune function, and neurological damage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recently published cohort study from AHA by Orkaby et al did not show a statistically significant relationship between frailty and AFIB [ 22 ]. In contrast, another study by Hang et al showed a statistically significant relationship between frailty and first-onset AFIB in patients with arterial hypertension [ 23 ]. The degree of frailty in the elderly and the development of AFIB share common pathophysiological mechanisms such as a strong inflammatory response, poor immune function, and neurological damage.…”
Section: Discussionmentioning
confidence: 95%
“…showed a statistically significant relationship between frailty and first-onset AFIB in patients with arterial hypertension [23]. The degree of frailty in the elderly and the development of AFIB share common pathophysiological mechanisms such as a strong inflammatory response, poor immune function, and neurological damage.…”
Section: Discussionmentioning
confidence: 97%
“…Frailty as a syndrome of reduced physical capabilities and enhanced vulnerability is a common phenomenon among older adults diagnosed with AF. On the one hand, frail patients are at higher risk for new-onset AF and on the other hand, frail patients already diagnosed with AF are at higher risk for all-cause death, ischemic stroke, and bleeding [ 11 , 12 ]. In addition to that, frail patients were less likely to be treated with oral anticoagulants, which might increase the risk of further thromboembolic complications [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frailty, as a syndrome that increases with age causes reduced physical capabilities and due to its relationship to AF, is an important component of current research. Frail patients are more prone to new-onset AF and those with pre-existing AF are at increased risk for serious adverse outcome events such as thromboembolic complications (ischemic stroke), bleeding, and all-cause death [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This model was validated in another study, which showed a close relationship between frailty status and incident atrial fibrillation. 11 According to the SPRINT 36-item FI, participants were categorized as frail (FI>0.21) or not frail (FI≤0.21). Patients were divided into 4 groups according to their treatment arms (intensive or standard) and frailty status (frail or not frail).…”
Section: Study Population and Designmentioning
confidence: 99%